STUDI NUMERIK DUCTED OPEN CENTER TURBINE SEBAGAI OCEAN RENEWABLE ENERGY - Rilo Farizky (2022)
This thesis presents an analysis using a numerical method of an open center tidal turbine with three-dimensional RANS simulation. The tidal turbine with open center type is modeled with a hole in the hub, with analysis using CFD capturing the vortex and blade resistance. The performance of the open center type tidal turbine is investigated for axial flow, looking for the value of the thrust generated in each turbine component. Then it's varied by modifying the turbine duct and varying the angle of attack on the hydrofoil. The value of the thrust obtained from the analysis results will be used to calculate the coefficient of the thrust which will later be made a graph of the coefficient of the thrust from low to high rotational speed Comparison of the graph of the coefficient of thrust in each variation will be seen which variation is the most optimal from these results.